1925
DOI: 10.1002/cber.19250580230
|View full text |Cite
|
Sign up to set email alerts
|

Hydrierung des Indols znm Perhydro‐indol und zum Hexahydro‐ o ‐äthyl‐anilin

Abstract: rgzg] WiEZstatter, S~i t z , u. B r a u n : Hydriemng & . s IpdoZ.8. 385 Die Bestimmung des Aluminiumoxydes geschieht am einfachsten aus der Differenz der Oxyde. Es kt wohl unter gewissen Voraussetzungen eine Fdlung des Aluminium-Ions als AlPO, moglich, da jedoch diese Bestimmungsform sich bekanntlich sehr wenig eignet, so m r d e davon Abstand genommen. Analgse des Hexahydro-o-lthyl-anilins: 0.1635 g Sbst.: 0.4524 g CO,, 0.1986 g H,O. -0.1008 g Sbst.: 0.2789 g CO,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1925
1925
1971
1971

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The latter effect predominates if nickel is the catalyst. Thus, Willstátter, Seitz, and v. Braun (406) found that with a nickel catalyst at 225°C. no octahydroindole was formed, but that continued hydrogenation past the dihydro stage yielded l-ethyl-2-aminocyclohexane, which v. Braun, Bayer, and Blessing (54) had erroneously thought to be octahydroindole.…”
Section: B Reductionmentioning
confidence: 97%
“…The latter effect predominates if nickel is the catalyst. Thus, Willstátter, Seitz, and v. Braun (406) found that with a nickel catalyst at 225°C. no octahydroindole was formed, but that continued hydrogenation past the dihydro stage yielded l-ethyl-2-aminocyclohexane, which v. Braun, Bayer, and Blessing (54) had erroneously thought to be octahydroindole.…”
Section: B Reductionmentioning
confidence: 97%